tRNA Modification and Genetic Code Variations in Animal Mitochondria - Kimitsuna Watanabe; Shin-ichi Yokobori (Journal of Nucleic Acids)
In animal mitochondria, six codons have been known as nonuniversal genetic codes, which vary in the course of animal evolution. They are UGA (termination codon in the universal genetic code changes to Trp codon in all animal mitochondria), AUA (Ile to Met in most metazoan mitochondria), AAA (Lys to Asn in echinoderm and some platyhelminth mitochondria), AGA/AGG (Arg to Ser in most invertebrate, Arg to Gly in tunicate, and Arg to termination in vertebrate mitochondria), and UAA (termination to Tyr in a planaria and a nematode mitochondria, but conclusive evidence is lacking in this case). We have elucidated that the anticodons of tRNAs deciphering these nonuniversal codons (tRNATrp for UGA, tRNAMet for AUA, tRNAAsn for AAA, and tRNASer and tRNAGly for AGA/AGG) are all modified; tRNATrp has 5-carboxymethylaminomethyluridine or 5-taurinomethyluridine, tRNAMet has 5-formylcytidine or 5-taurinomethyluridine, tRNASer has 7-methylguanosine and tRNAGly has 5-taurinomethyluridine in their anticodon wobble position, and tRNAAsn has pseudouridine in the anticodon second position. This review aims to clarify the structural relationship between these nonuniversal codons and the corresponding tRNA anticodons including modified nucleosides and to speculate on the possible mechanisms for explaining the evolutional changes of these nonuniversal codons in the course of animal evolution.